Enhancing School Quality Assurance through Educational Service Quality Management - Nur Laili; Sabar Narimo; Achmad Fathoni (LPPM STIE KRAKATAU, 2026)
School quality assurance is not determined solely by students’ academic achievement but also by the quality of educational services experienced by stakeholders, particularly parents. This study aims to analyze educational service quality through parental satisfaction surveys as a mechanism for school quality control. A quantitative approach with a cross-sectional survey design was employed. Data were collected through a structured questionnaire distributed to parents of students at SD Muhammadiyah Palur, Sukoharjo Regency, Indonesia. A total of 309 valid responses were analyzed using descriptive statistical techniques to identify satisfaction levels across various educational service indicators. The results indicate that overall parental satisfaction with educational services is relatively high. Core services, including classroom teaching and teacher–parent communication, received highly positive evaluations, while some supporting services showed more varied satisfaction levels. These findings suggest that educational service surveys can serve as effective data-driven instruments for monitoring school service performance and supporting decision-making within internal quality assurance systems. The study highlights the importance of stakeholder-oriented educational service management in promoting sustainable school quality improvement.